Pro- and Anti-oxidant Properties of Redox-Active Catechol-Chitosan Films - Kim, Eunkyoung; Kang, Mijeong; Liu, Huan; Cao, Chunhua; Liu, Changsheng; Bentley, William E.; Qu, Xue; Payne, Gregory F. (Frontiers in Chemistry, 2019)
Catechols are abundant in nature and are believed to perform diverse biological functions that include photoprotection (e.g., melanins), molecular signaling (e.g., catecholamine neurotransmitters), and mechanical adhesion (e.g., mussel glue). Currently, the structure-property-function relationships for catechols remain poorly resolved, and this is especially true for redox-based properties (e.g., antioxidant, pro-oxidant, and radical scavenging activities). Importantly, there are few characterization methods available to probe the redox properties of materials. In this review, we focus on recent studies with redox-active catechol-chitosan films. First, we describe film fabrication methods to oxidatively-graft catechols to chitosan through chemical, enzymatic, or electrochemical methods. Second, we discuss a new experimental characterization method to probe the redox properties of catechol-functionalized materials. This mediated electrochemical probing (MEP) method probes the redox-activities of catechol-chitosan films by: (i) employing diffusible mediators to shuttle electrons between the electrode and grafted catechols; (ii) imposing tailored sequences of input voltages to “tune” redox probing; and (iii) analyzing the output current response characteristics to infer properties. Finally, we demonstrate that the redox properties of catechol-chitosan films enable them to perform antioxidant radical scavenging functions, as well as a pro-oxidant (reactive oxygen-generation) antimicrobial functions. In summary, our increasing knowledge of catechol-chitosan films is enabling us to better-understand the functions of catechols in biology as well as enhancing our capabilities to create advanced functional materials.